Project-Based Learning in Basic Chemistry Practice: Its Impact on Vocational Students’ Analytical Abilities - Munawan, Amro Hafiz; Dewi, Citra Ayu; Suryati, (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Vocational chemistry education is expected to develop not only procedural competence but also higher-order analytical abilities aligned with industrial demands. However, Basic Chemistry Practice in vocational high schools is often dominated by teacher-centered instruction, limiting students’ capacity to interpret experimental data and connect theory with practice. This study aimed to examine the impact of Project-Based Learning (PjBL) on vocational students’ analytical abilities and to explore students’ and teachers’ perceptions of its implementation. A quantitative pre-experimental design using a one-group pretest–posttest model was employed. The participants were 34 Grade X Industrial Chemical Engineering students at a vocational high school. Analytical ability was measured using HOTS-based open-ended questions aligned with Bloom’s revised taxonomy, and perception data were collected through Likert-scale questionnaires. Statistical analysis included the Shapiro–Wilk normality test, paired sample t-test, and normalized gain (N-gain) analysis. The results showed a significant improvement in analytical ability, with the mean score increasing from 41.0 to 73.5 (p < 0.001) and an N-gain value of 0.55, categorized as moderate. Students and teachers reported highly positive perceptions, particularly regarding engagement, collaboration, and analytical skill development. These findings suggest that PjBL provides an effective pedagogical framework for strengthening analytical competence in vocational chemistry practice. The novelty of this study lies in the integration of HOTS-based assessment into authentic vocational chemistry projects within a PjBL framework, an approach that is still rarely reported in vocational chemistry education. By combining learner-centered project implementation with structured higher-order thinking assessment, this study offers a practical and context-relevant model for improving analytical competence in vocational education settings.